The Occurrence of Subsequent Malignancy in Patients Presenting with Deep Vein Thrombosis: Results from a Historical Cohort Study - Rajan, Raghu; Levine, Mark; Gent, Michael; Hirsh, Jack; Geerts, William; Skingley, Peter; Julian, Jim (Thrombosis and Haemostasis, 1998)
Background: Several studies have reported that patients who present with idiopathic deep vein thrombosis (DVT) have an increased risk of subsequently developing cancer. A clinical trial had previously been conducted examining the optimal duration of oral anticoagulant therapy following initial heparin treatment in patients with proximal DVT.Methods: A historical cohort study was performed on patients enrolled in the duration of anticoagulant trial. Patients known to have cancer at the time of entry into the trial were excluded. The qualifying DVTs were classified as idiopathic (no known associated risk factors) or secondary without knowledge of subsequent recurrent venous thrombosis or cancer. The patients were then followed for the development of cancer.Results: Thirteen (8.6%) of the 152 patients in the idiopathic cohort subsequently developed cancer compared to eight (7.1%) of 112 patients in the secondary cohort, P = 0.86. Two (5.4%) of 37 patients with recurrent venous thromboembolism and 19 (8.4%) of 227 patients without recurrent thromboembolism developed cancer, P = 0.7.Conclusion: Our study did not detect an increased risk of subsequent cancer in patients presenting with idiopathic DVT compared to secondary DVT; nor did we detect an increased incidence of cancer in patients with recurrent venous thromboembolism. Further studies are required prior to pursuing a policy of aggressive screening for cancer in patients with idiopathic venous thromboembolism.